Thursday

July 24, 2014

July 24, 2014

Posted by **NGOFAKA** on Tuesday, October 23, 2007 at 8:03am.

if sqrt(y)=(arctan)tan-1(x), show that (1+x^2)dy/dx((1+x^2)dy/dx)=2

**Related Questions**

calculus - Let f be a function defined by f(x)= arctan x/2 + arctan x. the value...

Pre Cal. - Evaluate tan(cos^(-1)(3/2 )+tan^(-1)(3/3))? arccos(sqrt(3) / 2...

Calculus - 1.Evaluate: (1/(x*sqrt(x^2-4)) I know the answer is -1/2*arctan(2/...

trigonometry - tan60=2 tan30/1-tan^2 30 sqrt(3)=I'm confused of that 2 but i ...

calculus - Now we prove Machin's formula using the tangent addition formula: tan...

PreCalculus - I'm unsure how to even start this problem Solve for x: Arctan( -4/...

calculus - Calculate definite integral of dx/(x^4 * sqrt(x^2 + 3)) Over (1,3) I ...

Maths - if sqrt(y)=(arctan)tan-1(x), show that (1+x^2)dy/dx((1+x^2)dy/dx)=2

limiting position of the particle - A particle moves along the x axis so that ...

calculus - can anyone tell me if tan-1x= 1 over tan x? No. They are different. ...